TEACHER'S WORK COMMITMENT TO IMPROVE MANAGEMENT AT STATE MADRASAH TSANAWIYAH 1 ASAHAN - Fachruddin Azmi; Rusydi Ananda; Dahlia Dahlia (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2019)
1) increased Madrasah-based management activities performedMadrasah head by making criteria or purpose and determination to plan theteaching program, conduct learning, evaluate learning, and guiding students; 2)supervision of teachers' work commitments from Madrasah Tsanawiyah Negeri1 Asahan is conducted routinely by examining teaching programs, monitoringteacher activity, and matching student progress reports teachers have madewith information from deputy head of Madrasah and students; 3) Assistance,guidance, and direction to solve the problem of performing the teachers’ dutiesby identifying the competency of the teacher, individual leadership inconsultation, mentoring the group through a meeting of teachers or delegationto the deputy's head experienced madrasahs and teachers;